Pengelolaan Dokumen Arsip Laboratorium Menggunakan OwnCloud Sebagai Media Cloud Storage Berbasis Infrastructure as a Service (IaaS) - Prita Haryani; Erfanti Fatkhiyah; Faulinda Ely Nastiti (JURIKOM (Jurnal Riset Komputer), 2023)
Archive document management of three laboratories namely Database Laboratory, Network Laboratory and Programming Laboratory under the Department of Informatics, Faculty of Information Technology and Business, Institute of Science & Technology Akprind Yogyakarta in managing laboratory archive documents still uses public applications, so they are vulnerable to exposure hack. In addition, the management of archival documents in each laboratory has not been managed centrally by the Informatics Department. Based on the problem of archival document management in each laboratory that has not been managed centrally by the Informatics Department and document storage that still uses public applications so it is vulnerable to being hacked, this research will develop an Infrastructure as a Service (IaaS) private cloud storage application. ) by using the OwnCloud application. The PPDIOO method developed by CISCO is used as a research method. The steps of the PPDIOO method are Prepare, which is preparing a work plan both from a technical and strategic point of view which is used to build a Cloud Server, Plan, which is a needs analysis used as a parameter before designing a private cloud network system, Design, which is making a design for monitoring virtual servers that will implemented on a cloud computing network, Implement is the process of building a Cloud Server using OwnCloud, Operate is the process of operating OwnCloud such as user management, uploading and downloading documents, and sharing documents with other users, and Optimize, namely the process of increasing capacity (storage, resources) according to needs users so that OwnCloud's performance is optimal. After testing using the blackbox testing method, the result is that the Cloud Computing application based on Infrastructure as a Service (IaaS) using OwnCloud can work properly starting from the login process to the process of storing data, uploading and downloading files and sharing files with other users. All forms and features work according to their function.